Mycobacterium tuberculosis: Readouts of bacterial fitness and the environment within the phagosome - Tan, Shumin (Methods Mol Biol, 2017)
Macrophages fulfill most of their microbicidal duties in their phagosomes following uptake of microbes. However, some microbes, such as Mycobacterium tuberculosis, have evolved mechanisms to subvert the normal maturation process of their phagocytic compartment to limit the hostility of this environment. The experimental analysis of this process, and its subsequent impact on bacterial fitness is technically-demanding and has required the development of a broad range of readouts to correlate function and outcome. In this chapter we detail two technically divergent platforms to measure the environment within the phagosomal compartment that contains Mtb in the short term, and more long-term readouts of bacterial fitness and Mtb’s reaction to host-derived stresses. The readouts are all fluorescence-based and are adaptable to measurement by a range of platforms, including spectrofluorometry, confocal microscopy and flow cytometry.